Interest in Learning Mathematics for Students of SMP Negeri 2 Tuntang Semarang Regency towards Learning During a Pandemic - Lu'luu Habibah As Sa'adah; Enika Wulandari (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
This research is motivated by indications of the less than ideal mathematics learning performance of class VIII students of SMP Negeri 2 Tuntang in the 2021/2022 academic year in online learning. The goal to be achieved in this research is to find out how the interest in learning mathematics in class VIII SMP Negeri 2 Tuntang is during the Covid-19 pandemic. This research uses an approach approach. Data collection was carried out by distributing questionnaires as instruments for preliminary studies, interviews and documentation. Data were analyzed through data reduction, data presentation and conclusion drawing. Testing the validity of the data is done by technical triangulation. The results showed that the interest in learning mathematics in grade VIII SMP N 2 Tuntang during the pandemic was categorized as high and medium interest. Students in the high interest category do not like online learning, have an interest in online learning, are involved in online learning, have an interest in online learning. The students in the category of moderate interest, do not like online learning, have an interest in online, have poor interaction in discussion and collection activities but have good involvement in asking about material to friends or teachers, and lack attention to online learning.